Effect of Different Doses of Nitrogen and Phosphorus on The Corm and Cormel Development of Gladiolus (Gladiolus sp.) cv. American Beauty - Pant, SS (Journal of the Institute of Agriculture and Animal Science, 2005)
A study was conducted to evaluate the effect of different doses of nitrogen and phosphorus on the development of corm and cormel of gladiolus at the Horticulture Farm, IAAS, Rampur in 2002. Diameter, thickness and weight of the corms, and cormels were measured after 150 days of planting and the effect of nitrogen and phosphorous fertilizers was assessed. The nitrogen dose of 50 kg/ha produced the highest corm yield (17.71 g/plant), where as higher dose of nitrogen (100 and 150 kg/ha) fertilizer produced the lowest cormel yield. Variable doses of phosphorous did not produce any significant effect on corm diameter and corm thickness but it produced a significant effect on corm height and cormel yield per plant. Higher doses of phosphorous fertilizer (50 and 100 kg/ha) produced the highest yield as compared to the control. It appears that corm and cormel respond better to the higher doses of phosphorous fertilizer compared to the nitrogenous fertilizer. A significant interaction effect was observed on cormel weight. The phosphorous at 100 kg/ha and nitrogen at 0 kg/ha produced the highest cormel yield (25 g/plant), whereas nitrogen at 150 kg/ha and phosphorous at 0 kg/ha produced the lowest cormel yield (1.95 g/plant). The interaction effect suggests that cormel yield responds better to the higher level of phosphorous combined with lower level of nitrogen. Key words: Nitrogen, phosphorous, corm, cormel, gladiolus J. Inst. Agric. Anim. Sci. 26: 153-157 (2005)